Social Variables and Economic Success: the Case of Italian Industrial Development - Giovanni Peri (University of California, Department of Economics, 2004)
Italy makes for a very interesting case study of the impact of social variables on economic performance. Across its provinces, differences in social and cultural attitudes seem associated to large differences in economic development. We analyze the importance of some social variables on industrialization and on employment creation across 95 Italian provinces during the period 1951-1991. On one hand we find little evidence that civic involvement (Social Capital) was associated with industrial and economic development. On the other hand we find strong evidence that organized crime, measured as high murder rates, was negatively correlated with industrial and economic development. We use measures of murder rates in the distant past to suggest that the correlation captures, at least in part, a stable and possibly causal link between organized crime and lack of employment growth.
Keywords: O52; Z13; R3; 330; Industrial Development; Regional Productivity; Italian Provinces; Civic Spirit; Murder Rates; Industrialisierung; Social Capital; Kriminalität; Regionale Entwicklung; Italien